Allocation of pond area for Bangus production a linear programming approach - Go, Gideon Pallanan (2007)
Aquaculture managers are faced with the problem of efficiently using the company?s pond to cater for various marine products demanded by the market, and at the same time maximize profitability. While this allocation task is crucial, many aquaculture managers still follow an unsystematic or intuitive method of doing this. This study was created to present aquaculturists with a mathematical approach of allocating limited area of pond to the production of different fish products demanded by the market. Specifically, an LP model was formulated to allocate a 100-hectare area of pond to the production of three Bangus products over a one-year and a two-year production timeframe. Moreover, for sets of selling price were considered, taken one at a time for the one year time-frame, and successively for the two-year time frame. Optimal solution is the identification of the succession by which the products are to be produced during the given time frame. Altogether, the model formulated outperforms the conventional method, in that the model simultaneously exhausted all possible subdivision of the pond area, as well as all feasible production succession, in finding optimum allocation solution. With this method, aquaculture mangers can maximize the capability of their ponds to cater the demands of the market. In the end, overproduction and underproduction will be avoided, market demands met, and profit maximized.
Thesis (BS Applied Mathematics) -- University of the Philippines Mindanao, 2007
Keywords: Bangus; Bangus -- Production; Aquaculture; Programming; Linear programming; Mathematical modelling